Penyuluhan Kesantunan berbahasa sebaga Upaya pencegahan Perundungan Verbal di SMP Negeri 3 Bandar Sei Kijang - Fatmawati, Fatmawati; Apriani, Leni; Ningsih, Rika; Alfi, Faiza Riskia; Humairah, Fanisa Rania (UIR Press, 2025)
This PkM activity was motivated by the PkM team's concerns regarding the rampant verbal bullying in educational units. This PkM activity aims to provide awareness to students about the importance of implementing polite language as an effort to prevent verbal bullying. The PkM activity was carried out at SMP Negeri 3 Bandar Sei Kijang. The PkM participants numbered 22 students. The PkM activity lasted for one day, namely December 16, 2024. The PkM team consisted of five people consisting of three lecturers and two students. All members of the PkM team came from the Faculty of Teacher Training and Education, Riau Islamic University. The PkM method uses an educational approach in the form of counseling and mentoring. The PkM activity began with the delivery of counseling material on polite language as an effort to prevent verbal bullying. Furthermore, PKM participants were invited to discuss and fill out a questionnaire that had been prepared by the PkM team. The PkM results showed that the PkM activity ran smoothly and all PkM participants were actively involved and enthusiastic in participating in the series of PkM activities. PkM participants agreed that verbal bullying is done by using words to mock, belittle, or insult others. PkM participants stated that they had experienced verbal bullying and had been perpetrators of verbal bullying. Furthermore, PkM participants stated that the school environment is an environment where verbal bullying often occurs. Finally, PkM participants agreed that the application of polite language can reduce verbal bullying.